Clinical Tools for Assessing One-Handed Skills in Children With Cerebral Palsy: An Umbrella Review - Samira Boroumand; Marzieh Pashmdarfard; Dorsa Hamedi; Afsoon Hassani Mehraban (Occupational Therapy International)
Conclusion: This study showed that among the numerous tools available for assessing one-handed skills in children with CP, only a limited number have excellent evidence for overall clinical utility. These findings can serve as a basis for selecting more precise, evidence-based tools in the assessment, and rehabilitation interventions for these children.